Multi-Objective Optimization of Daylighting–Thermal Performance in Cold-Region University Library Atriums: A Parametric Design Approach - Yunong Gao; Shuting Zhao; Yong Huang; Hui Pan (Energies)
Open atrium spaces in university libraries have emerged as a prevalent architectural trend. While increasing daylighting through enlarged glazing areas enhances the indoor environment, it simultaneously introduces significant thermal challenges in cold regions where environmental comfort demands lead to higher energy loads. This study investigates the optimization of daylighting–thermal performance balance through a multi-objective parametric approach to address the inherent conflicts between environmental quality and energy efficiency in atrium design. In this paper, we take the library project in the cold region as a practical case, use the measured data to support the simulation experiment, combine the parametric platform and multi-objective coupling optimization algorithm to carry out digital modeling, and explore the dynamic relationship between the atrium light, heat environment, and the value of energy consumption under the influence of a variety of parameters. The experimental results show that the quality and energy efficiency of the atrium light environment are improved after parameter optimization. The energy consumption per unit area (EUI) is reduced by 84.84 kwh/m2–106.83 kwh/m2 while the adequate natural illuminance (UDI) is increased by 5.06–27.64%, which confirms the feasibility of the research and development of the building light–heat coupling optimization technology route and program module. This paper aims to explore the quantitative law of design elements on light–heat balance at the early stage of architectural design and to provide a theoretical basis and reference blueprint for improving the comprehensive decision-making ability of architects in sustainable design and realizing integrated and efficient program decision-making.